The Role of Leadership and Organizational Culture in the Successful Implementation of Total Quality Management in the Educational Environment - Hafid M Talla, Abd; Wirayama, Agung; Ananda, Asti (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
The implementation of Total Quality Management (TQM) in education requires a holistic approach that involves visionary leadership and a collaborative organizational culture. Total Quality Management (TQM) has been adopted in the education sector to improve learning quality, administrative efficiency, and stakeholder satisfaction (students, parents, and the community). However, its implementation is often hampered by bureaucratic resistance, lack of teacher training, and hierarchical organizational culture. This article analyzes how transformational leadership and learning-based culture play a role in improving the quality of education through TQM. The research uses a qualitative approach with a comparative case study design to analyze the role of leadership and organizational culture in the implementation of Total Quality Management (TQM) in educational institutions. Data were collected through semi-structured interviews with participants (principals, teachers, students, staff), participatory observation of TQM activities (such as coordination meetings and quality workshops), and analysis of policy documents and quality reports. The selection of participants is carried out purposively with the criteria of a minimum of two years of involvement in the TQM program. The data were analyzed thematically using NVivo 12 software through the stages of transcription, coding, and source triangulation to validate the findings, this study reveals that the success of TQM is determined by the leader's ability to empower stakeholders as well as the culture that supports pedagogical innovation. These findings provide practical recommendations for educational institutions to optimize TQM through the integration of participatory leadership and performance-based reward systems.